2007
DOI: 10.21248/zaspil.47.2007.348
|View full text |Cite
|
Sign up to set email alerts
|

On the control/raising ambiguity with aspectual verbs: a structural account

Abstract: In what follows, I first briefly review Perlmutter (1968, 1970), in which it is argued that aspectual verbs are ambiguous between control and raising. I suggest that while the argument for the raising analysis is solid, the arguments supporting the control analysis of aspectual verbs are less so. As an alternative hypothesis to consider, I introduce the structural ambiguity hypothesis. In Section 3, I review three recent analyses of control and raising. Although there are important differences among them, they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Note that a tendency can be observed with regard to the voice of the aspectual verb: for example, the verb pauō (active voice) [that belongs to the ifrst group of aspectuals] can take an in ifnitive or a participle as its complement; while pauomai (mediopassive voice) appears to select a participle as complement. This distribution accords with Fukuda (2007), who has shown that aspectual verbs in the passive should be more natural with aspectuals in L-Asp (+participials) 12) We have not included ekleipō in our indicative list, given it seems that most of the uses of ekleipō do not involve any of the basic aspectual meanings we are dealing with (start-continue-stop).…”
Section: Aspectuals In Ancient Greek and Fukuda's Analysissupporting
confidence: 81%
See 3 more Smart Citations
“…Note that a tendency can be observed with regard to the voice of the aspectual verb: for example, the verb pauō (active voice) [that belongs to the ifrst group of aspectuals] can take an in ifnitive or a participle as its complement; while pauomai (mediopassive voice) appears to select a participle as complement. This distribution accords with Fukuda (2007), who has shown that aspectual verbs in the passive should be more natural with aspectuals in L-Asp (+participials) 12) We have not included ekleipō in our indicative list, given it seems that most of the uses of ekleipō do not involve any of the basic aspectual meanings we are dealing with (start-continue-stop).…”
Section: Aspectuals In Ancient Greek and Fukuda's Analysissupporting
confidence: 81%
“…Sevdali (2007) who argues (a) that all in ifnitives in Ancient Greek are CPs, and (b) that there is a split between two types of CPs, normal C*Ps (strong phase) that have a contrastive focus feature and Control in ifnitives that do not have this feature and consequently do not have availability of accusative for the in ifnitival subject. 19) That is similar to the analysis of gerundives of Modern English as more limited than in ifnitives with respect to a range of possible interpretations (Bolinger 1968, Freed 1979, Brinton 1988, Fukuda 2007. In English, states are natural with in ifnitives but often unnatural with gerundives.…”
Section: Aspectuals In Ancient Greek and Fukuda's Analysismentioning
confidence: 57%
See 2 more Smart Citations
“…In (29), for example, the individual who is careful and who is under an obligation can be either John or the doctor. Indeed, some previous authors have ascribed crossed reading to the auxiliary status of mau and other words meaning "want" (Isamu Shoho 1995;Shin Fukuda 2007;Simon Musgrave 2001;Hirobumi R. Sato 2004). For mau, the authoritative dictionary Kamus Besar Bahasa Indonesia (KBBI) lists its intention/desire meaning as adverbia, which includes auxiliaries as well as adverbs.…”
Section: Clause Structurementioning
confidence: 99%